Metode Pemindahan Alat Bor Pada Eksplorasi Nikel Laterit untuk Efisiensi Operasional dan Optimasi Lokasi Pengeboran - Risal Gunawan; Mirawati Nur Wulandari (Program Studi Teknik Pertambangan, Fakultas Teknik, Universitas Sulawesi Tenggara, 2025)
Lateritic nickel exploration is a crucial step in determining the sustainable potential of mineral resources. One of the main challenges in lateritic nickel exploration is selecting an efficient and accurate drilling method to identify nickel concentrations within the laterite layer. This research focuses on the moving rig method, a dynamic drilling equipment relocation technique applied at different locations to optimize the explored area. The study aims to evaluate the effectiveness and efficiency of the moving rig method in lateritic nickel exploration by considering factors such as the type of drilling equipment, drill point determination, rig pacing before relocation, communication with road supervisors, and the moving and setting process of the drilling equipment. The findings indicate that the application of the moving rig method can enhance drilling efficiency, reduce the time required for lateritic nickel exploration, and ensure more precise drilling depth and location. However, challenges related to geological constraints and soil characteristics must still be considered in its implementation.